OFÍCIO DE PROFESSOR: ENTRE O ARTÍFICE E O ARTISTA – UMA ANÁLISE ADORNIANA - Santos, Leônidas Melo (2018)
This work proposes to reflect on the teaching activity, the formation and the emancipatory education, having as parameter the work of the artist and the aesthetic dimension of the education. To make this attempt, we resorted to bibliographic research. The work of Theodor W. Adorno is the main source of research. The thoughts of Theodor Adorno, as well as the other members of the Critical Theory of Society, are essential to unveil the ideological relations that make up society, especially in the midst of new configurations, marked by the predominance of the cultural industry and the increasing destitution of individuality. Thinking about the teacher and his professional practice has been recurring for some time. Comenius carried out this process in the seventeenth century, in his work Didactic Magna. In the work in question, the thinker equates the art of teaching with the activity of the craftsmen, which meant some advances in relation to the valorization of the method and the systematization of teaching. However, there was also an attempt to instrumentalize teaching and the submission of educational purposes to the demands made by the new labor organizations, which were consolidating at the time. In this work the activity of the teacher analogous to the activity of the artist is conceived, as a professional capable of performing a teaching practice consistent with emancipatory education. In these conditions, the teacher as well as the artist, applies to the interiority of his object and prizes for the valorization and preservation of the internal qualities of his student. The artist teacher does not submit to the needs originated by the administered society, in addition, it promotes resistance to external determinations. Therefore, in the midst of the predominance exercised by technical rationality in the social environment, ensuring the possibility of effective emancipation. This process makes possible the overcoming in relation to the social logic promoted by the technical rationality and causes the subjects to release their consciousness of the ideological ties, that promote the semiformation. To the extent that the teacher resists external determinations to apply in the development of the student's inner qualities, he contributes to the emancipation of society as a whole, for an emancipated society demands emancipated individuals, hence the possibility of emancipation of society passes first by the emancipation of each subject.